2006
DOI: 10.1111/j.1346-8138.2006.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of a laser device called fractional photothermolysis system for acne scars

Abstract: Ablative laser resurfacing is an effective treatment for acne scars. However, edema and prolonged erythema are common. Additionally, scarring and hyperpigmentation are often induced. A new concept of laser called fractional photothermolysis has been designed to create microscopic thermal wounds to achieve skin rejuvenation without significant side-effects. We treated 10 patients with acne scars using this laser system (Reliant Fraxel SR Laser). All the patients were successfully treated with minimal adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0
7

Year Published

2008
2008
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 33 publications
(47 reference statements)
5
84
0
7
Order By: Relevance
“…Moreover, the undesirable side effects of the very effective original ablative laser resurfacing fostered the use of FP in the treatment of scars, and, so far, various studies have examined its effect on different scar types. For acne scars, ten patients treated with non-ablative FP for up to three times at 2-3 week intervals all showed clinical improvement 4 weeks after treatment [23]. In a larger study by Alster et al 53 patients with atrophic scars were treated with non-ablative FP on a monthly basis for two or more treatments.…”
Section: Non-ablative Fractional Photothermolysis Lasermentioning
confidence: 99%
“…Moreover, the undesirable side effects of the very effective original ablative laser resurfacing fostered the use of FP in the treatment of scars, and, so far, various studies have examined its effect on different scar types. For acne scars, ten patients treated with non-ablative FP for up to three times at 2-3 week intervals all showed clinical improvement 4 weeks after treatment [23]. In a larger study by Alster et al 53 patients with atrophic scars were treated with non-ablative FP on a monthly basis for two or more treatments.…”
Section: Non-ablative Fractional Photothermolysis Lasermentioning
confidence: 99%
“…Fractional non-ablative treatments have been useful in treating conditions such as mild to moderate rhytides [10], photodamaged skin [11], acne scarring [12,13], leucodermic scars [14], melasma [15,16], and nonfacial skin rejuvenation [17]. Investigators have reported re-epithelization in 24 hours with this procedure [18,19], thereby reducing downtime for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has changed the light-based treatment paradigm from that of layers of photothermolysis to one of columns of thermal damage. Recently, an erbium-doped fiber laser, emitting light at 1,550 nm, has been shown to be effective in the treatment of photodamaged skin, acne scars, post-surgical scarring, poikiloderma of Civatte, pigmented lesions, striae distensae, as well as melasma [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%